The History of the Eastern Smelting Company Limited with particular reference to the Malayan ( Malaysian ) Tin Industry from 1869 to 1966 with an emphasis between the years 1946 to 1966 - Ibrahim, Mohamed Ismail (Universiti Sains Malaysia, 1973)
Therefore, this paper, I should say, is an attempt to show the dealings of the Syarikat Eastern Smelting in the context of the whole Malaysian setting.